Navigating identity and education: narratives of LGBTQ+ educators in the southern United States - Coronado, David Lee (My University, 2025)
This qualitative research explored the lives of five LGBTQ+ educators in the United States South. One participant identified as gay, one as bisexual, one as lesbian, one as transgender, and one as queer. In addition to the lived experiences, a document analysis of proposed, passed, and dead legislation was conducted in conjunction with the interviews to better understand the lived experiences of the LGBTQ+ participants through their perspectives and from a legislative perspective. Drawing on Minority Stress Theory, Intersectionality, and Queer Theory, this qualitative study examined how lived experiences of being an LGBTQ+ educator shapes participants’ pedagogies and subjectivities. Findings reveal that LGBTQ+ educators’ professional identity rather than their personal identity of being an LGBTQ+ person influences their desire to stay in field of education although many policies and legislation are discriminatory to them as people. Participants discussed their levels of professional commitment to the field of education, their feelings of belonging in educational workplaces, couched within salient, intersecting identity dimensions related to sexual orientation, gender, race, and dis/ability. Recommendations for further research encourage educational institutions to support LGBTQ+ educators beyond “food, festivals, and flags” (C. F. Meyer & Rhoades, 2006), recognizing and amplifying the salience of intersecting identity dimensions of LGBTQ+ educators, and to dismantle systemic anti-gay and discriminatory systems threatening the pedagogies and existence of LGBTQ+ educators.
Keywords: LGBTQ+ educators; Minority Stress Theory; Intersectionality; No Promo Homo; LGBTQ+ legislation